2016
DOI: 10.1111/agec.12225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microcredit and other loans on female empowerment in Bangladesh: the borrower's gender influences intra‐household resource allocation

Abstract: This article examines microcredit's effectiveness in empowering women borrowers in rural Bangladesh. It does so by examining how genderspecific borrowing activities influence household expenditures which are either specifically of interest to men or women, and by examining the effects of all loans rather than only those provided by microcredit organizations. The article uses a quasi-experimental design to identify the effects of borrowing by men and women by using an original combination of panel data and inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…Ward‐level or other regional characteristics were previously used as instruments for endogenous household variables (e.g. Porter, ; Arslan et al ., ; Hirvonen and Hoddinott, ; Ma et al ., ). The advantage of regional instruments is that they are usually not influenced by individual households, so they are less likely to be endogenous than household‐level instruments.…”
mentioning
confidence: 99%
“…Ward‐level or other regional characteristics were previously used as instruments for endogenous household variables (e.g. Porter, ; Arslan et al ., ; Hirvonen and Hoddinott, ; Ma et al ., ). The advantage of regional instruments is that they are usually not influenced by individual households, so they are less likely to be endogenous than household‐level instruments.…”
mentioning
confidence: 99%
“…A spouse's decision of participating in nonfarm work is a risk coping strategy to secure necessities during shortfalls (Abdulai & Delegado, ). Moreover, women are considered for prioritizing providing food for their family over other nonfood expenditures, compared to men (Kennedy & Haddad, ; Porter, ). Accordingly, an increase in women's income share has been established to have a positive impact on household food budget share (Hoddinott & Haddad, ).…”
Section: Background On Nutrition Security In Indiamentioning
confidence: 99%
“…He found that, microcredit empowered the women regarding skill development, strengthening the self confidence level and contribution in family's decision making [13]. Porter describes the influences of the gender of the borrowers in taking the decision of the allocation of resources for the expenditures [14]. Jinia inspect that whether the microcredit increase the power of women in the decision making of the family or not?…”
Section: Literature Reviewmentioning
confidence: 99%